Personal Development of Future Psychologists: Role of Reflection in Structure of Ego Identity - Marina Solobutina (ARPHA Proceedings, 2022)
This study examined the ego identity and the types of reflection among students of the faculty of Psychology. To study the problem, the research methods used were as follows: Differential Diagnosis of Reflection, Method “Per-sonal Identity”, Personality Maturity Questionnaire. Differential Diagnosis of Reflection was used to diagnose the type of reflection as a stable personality trait. It was revealed that the prevailing type of reflection of students-psychologists was systemic. Systemic reflection was the only stable indicator of the level of personality maturity. Quasi-reflection and Introspective reflection did not depend on the level of personal maturity of the respondents. It was found that students of the faculty of Psychology had mainly an average degree of congruence of ego identi-ty. Emotional-motivational and behavioral components prevailed over the cognitive one in the structure of partici-pants’ ego identity. Students had a satisfactory level of personality maturity. Leading student’s needs were defined as in communication, in achieving one's goals and professional recognition. Correlation between the congruence of the ego identity and types of reflection of students-psychologists was revealed. With an average and high level of personality maturity, students valued their abilities, qualities and achievements, perceived the world and people holistically, established deep contacts with people. They strove to acquire knowledge about the world around them, showed flexibility and spontaneity in behavior, they were open to new experience and relatively independ-ent in their actions.